2019
DOI: 10.1108/apjml-05-2018-0190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the moral mechanism to purchase counterfeit luxury goods: evidence from China

Abstract: Purpose The purpose of this paper is to extend the theory of reasoned action and the theory of planned behaviour to measure the effects of ethical and moral antecedents (e.g. integrity, moral judgement, extrinsic religiosity and intrinsic religiosity, and ethical concern) on attitudes towards counterfeit luxury products. Additionally, it also measured the effects on attitudes towards purchase intention. Design/methodology/approach The scope of the study is the Chinese market. The sample size for the study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 89 publications
6
63
0
Order By: Relevance
“…Thus, our results can be stated as the indirect effect of subjective norms on the intention to purchase green products is affected by moral norms (Mathieu and Taylor, 2006; Yen et al , 2017). This may be an interesting finding as the previous literatures suggest that moral cues (e.g., moral norms and moral identity) affect the intention to purchase Fairtrade products (Yen et al , 2017), EFFL products (Jung et al , 2016) and energy-efficient appliances (Nguyen et al , 2017), and that moral norms could promote charitable behaviours (Chua et al , 2016; Reed et al , 2007; Jiang et al , 2019). However, this research found that in a collectivist culture, consumers with subjective norms affected the intention to purchase green products through moral norms.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, our results can be stated as the indirect effect of subjective norms on the intention to purchase green products is affected by moral norms (Mathieu and Taylor, 2006; Yen et al , 2017). This may be an interesting finding as the previous literatures suggest that moral cues (e.g., moral norms and moral identity) affect the intention to purchase Fairtrade products (Yen et al , 2017), EFFL products (Jung et al , 2016) and energy-efficient appliances (Nguyen et al , 2017), and that moral norms could promote charitable behaviours (Chua et al , 2016; Reed et al , 2007; Jiang et al , 2019). However, this research found that in a collectivist culture, consumers with subjective norms affected the intention to purchase green products through moral norms.…”
Section: Discussionmentioning
confidence: 57%
“…Emotionally stable persons are more relaxed, so they are less vulnerable to distress and impulsive behavior (McCrae and Costa, 2008). Impulsive buying behavior and emotional instability are positively correlated (Shahjehan et al, 2012;Jiang et al, 2019). Individuals with a high level of emotional instability suffer from anxiety and irritability, which makes them more vulnerable to impulsive buying behavior (Silvera et al, 2008).…”
Section: Personality Traitsmentioning
confidence: 99%
“…For example, Al-Khatib et al (2005) have found that even among customers from Arab countries of Saudi Arabia, Egypt, Kuwait and Oman, their attitudes, ethical beliefs and ideologies differ significantly. Moreover, in China, Jiang et al (2019) have found that there are many ethical and moral factors (such as integrity, moral judgment, extrinsic and intrinsic religiosity) that need to be considered by researchers in an all-encompassing way when determining consumer attitudes toward purchasing counterfeit luxury products (ATPCLP).…”
Section: Background Of Counterfeit Luxury Products Industrymentioning
confidence: 99%